Pengaruh Intellectual Capital Terhadap Produktivitas, Profitabilitas, Nilai Pasar Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Wany, Eva (UNIVERSITAS NEGERI SURABAYA, 2010)
AbstractThe research to testing and analysis the influence of intellectual capital to productivity, profitability, market value, to testing and analysis the influence of intellectual capital to market value with productivity as intervening variable, to testing and analysis the influence of intellectual capital to market value with profitability as intervening variable of manufacture company listed in Indonesia Stock Exchange. The sample of this study consists of 48 financial company listed in Indonesia Stock Exchange in period 2005-2007. The research data is analysis by using descriptive technique and tested by using using multiple regression analysis. Result of test of simple linier regression model proves that intellectual capital influence does not productivity, intellectual capital influence to profitability, intellectual capital influence to market value, intellectual capital influence to market value with productivity as intervening variable but direct influence productivity don't overweening influence to market value, intellectual capital influence to market value with profitability as intervening variable and direct influence profitability to market value statistically proven signifikan.